High-strength impermeability concrete and cement pole

By adopting high-strength anti-seepage concrete formula in concrete and using polymerization reaction and fiber modification technology to form polymer films with high strength and weather resistance, the problems of waterproof and impermeability reduction of concrete are solved, and significant improvements in mechanical strength and impermeability are achieved.

CN116409970BActive Publication Date: 2025-03-14JINING TIANCHEN ELECTRIC POWER EQUIPMENT CO LTD

Patent Information

Application Number
CN202310377461.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-03-14
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

Due to the microstructure difference between cement slurry and aggregate in concrete, pores and microcracks are present inside. When affected by the external environment, waterproof and impermeability resistance are reduced and service life is affected.

Method used

High-strength anti-seepage concrete formula, including gel materials, aggregates, epoxy resin emulsions, hydroxyacrylate emulsions, aliphatic organic amines, epoxy basalt fibers, calcium sulfaluminate and ethanolamine modified metakaolin, are used to form polymer films with high strength and weather resistance, filling pores and microcracks, and improving anti-seepage performance.

Benefits of technology

It significantly improves the mechanical strength and waterproof and impermeability of concrete, extends the service life, and effectively prevents and weakens the growth of cracks under the influence of external environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116409970B_ABST
    Figure CN116409970B_ABST
Patent Text Reader

Abstract

The invention relates to the field of concrete materials, in particular to a high-strength impermeable concrete and a cement pole, which comprises, by weight, 500-600 parts of gel material, 1400-1600 parts of aggregate, 100-120 parts of epoxy resin emulsion, 20-30 parts of hydroxy acrylate emulsion, 5-10 parts of aliphatic organic amine, 50-80 parts of epoxy basalt fiber, 5-10 parts of calcium sulfoaluminate, 10-20 parts of ethanolamine-modified metakaolin, 1-5 parts of polycarboxylate water reducer and 100-120 parts of mixing water. The high-strength impermeable concrete prepared by the invention has excellent mechanical strength and excellent waterproof and impermeability performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete materials, in particular to high-strength impermeability concrete and cement poles. Background Art

[0002] Concrete is one of the most important civil engineering materials in contemporary times. It is an artificial stone made of cementitious materials, granular aggregates (also called aggregates), water, and admixtures and additives added when necessary in a certain proportion, and is evenly mixed, compacted, and hardened. Concrete has the characteristics of abundant raw materials, low price, and simple production process. At the same time, concrete also has the characteristics of high compressive strength, good durability, and a wide range of strength grades. It is not only used in various civil engineering projects, but also widely used in power transmission, ship machinery, road transportation, geothermal engineering and other fields.

[0003] However, the microstructure of the cement paste adjacent to large-particle aggregates and fibers in concrete is usually quite different from the cement paste or mortar body in the system. Due to the differences, there are different numbers of pores and microcracks inside the concrete. When the concrete is affected by the external environment, the microcracks are easy to expand, resulting in reduced waterproof and anti-seepage properties of the concrete, and affecting its service life. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a high-strength impermeable concrete and a cement pole.

[0005] The technical solutions adopted are as follows:

[0006] A high-strength impermeability concrete, measured by weight, comprising:

[0007] 500-600 parts of gel material, 1400-1600 parts of aggregate, 100-120 parts of epoxy resin emulsion, 20-30 parts of hydroxy acrylate emulsion, 5-10 parts of aliphatic organic amine, 50-80 parts of epoxy basalt fiber, 5-10 parts of calcium sulfoaluminate, 10-20 parts of ethanolamine-modified metakaolin, 1-5 parts of polycarboxylic acid water reducer, and 100-120 parts of mixing water.

[0008] Furthermore, the gel material comprises cement and fly ash, and the weight ratio of the cement to the fly ash is 5-10:1.

[0009] Furthermore, the preparation method of the hydroxyacrylate emulsion is as follows:

[0010] Mix part of the mixed monomer, part of the emulsifier and water evenly, heat to 70-80°C, add part of the initiator and keep warm for 1-2 hours to obtain a seed emulsion, adjust the pH of the seed emulsion to 7-8, mix the remaining initiator with water, mix the remaining mixed monomer with the remaining emulsifier, and add the two obtained mixed solutions dropwise to the seed emulsion at the same time. Continue to keep warm for 2-4 hours, then adjust the pH of the system to 7-8, filter and discharge.

[0011] Furthermore, the mixed monomer includes methyl methacrylate, butyl acrylate, methacrylic acid, and hydroxypropyl methacrylate.

[0012] Furthermore, the weight ratio of methyl methacrylate, butyl acrylate, methacrylic acid and hydroxypropyl methacrylate is 60-80:20-30:3-5:1.

[0013] Furthermore, the aliphatic organic amine is one or more combinations of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, and trimethylhexamethylenediamine.

[0014] Furthermore, the preparation method of the epoxy basalt fiber is as follows:

[0015] The basalt fiber is hydroxylated with a piranha solution, and then dispersed in an amide organic solvent. In a protective gas atmosphere, the temperature is raised to 45-55°C, N'N-carbonyldiimidazole is added, and the reaction is stirred for 8-12 hours. Then, epichlorohydrin is added to the reaction solution, and the reaction is continued for 10-15 hours. After returning to room temperature, it is filtered, and the obtained solid is washed with ethanol and then dried.

[0016] Furthermore, the preparation method of the ethanolamine-modified metakaolin is as follows:

[0017] Disperse metakaolin in water to prepare a suspension, then drop an ethanolamine aqueous solution into the suspension, heat to 50-70° C., stir for 6-10 hours, filter, wash with water, and then dry.

[0018] Furthermore, the preparation method of the above-mentioned high-strength impermeability concrete is as follows:

[0019] The polycarboxylic acid water reducer and mixing water are mixed and stirred evenly to obtain a liquid premix, and then the gel material, aggregate, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix and stirred evenly to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and aliphatic organic amine are added to obtain a mixed material and mixed evenly.

[0020] The present invention also provides a cement pole, comprising the above-mentioned high-strength impermeability concrete.

[0021] Beneficial effects of the present invention:

[0022] Epoxy resin emulsion can be cured by polymerization reaction at room temperature and in a highly alkaline environment. After curing, it has high strength, good weather resistance, and is also resistant to water, acid, alkali and most chemicals. It is a polymer material often used in concrete modification. Aliphatic organic amines are not only curing agents for epoxy resins, but also have the functions of accelerating the hydration of cement minerals and inhibiting chloride ion corrosion. The hydroxyl groups in hydroxy acrylate emulsions can promote the curing of amines, and can form a mutually cross-linked three-dimensional network after curing with epoxy resin emulsions. This spatial network structure connects cement hydration products and aggregates together, improves the structural morphology of concrete, improves the crack resistance and compactness of concrete, and provides sufficient mechanical support for concrete. When concrete is affected by the external environment, it is conducive to the dispersion and transfer of stress, and the growth of cracks is prevented and weakened. The formed polymer film can improve the interface transition zone, fill the pores and micro cracks inside the concrete, and play a role in waterproofing and anti-seepage. The addition of epoxy basalt fiber can improve the mechanical properties of concrete, and the presence of epoxy groups on the surface enables it to participate in the formation process of the polymer network, improve its stability and reduce slippage under the action of external forces. Ethanolamine-modified metakaolin can reduce the porosity of concrete, accelerate the early hydration of cement, and enhance the ability of the system to resist strain caused by shrinkage. After testing, the high-strength anti-seepage concrete prepared by the present invention has excellent mechanical strength and excellent waterproof and anti-seepage properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a microstructure diagram of the concrete prepared in Example 1 of the present invention. The arrows indicate epoxy basalt fibers tightly wrapped by hydration products. DETAILED DESCRIPTION

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The technologies not mentioned in the present invention are all referenced to the prior art.

[0025] At present, the microstructure of cement paste adjacent to large-particle aggregate in concrete is usually quite different from that of the cement paste or mortar body in the system. Due to this difference, there are different numbers of pores and microcracks inside the concrete. When the concrete is affected by the external environment, the microcracks are easy to expand, resulting in reduced waterproof and anti-seepage properties of the concrete, and seriously affecting its service life.

[0026] In order to solve the above problems, the present application provides a high-strength impermeability concrete, which comprises, by weight:

[0027] 500-600 parts of gel material, 1400-1600 parts of aggregate, 100-120 parts of epoxy resin emulsion, 20-30 parts of hydroxy acrylate emulsion, 5-10 parts of aliphatic organic amine, 50-80 parts of epoxy basalt fiber, 5-10 parts of calcium sulfoaluminate, 10-20 parts of ethanolamine-modified metakaolin, 1-5 parts of polycarboxylic acid water reducer, and 100-120 parts of mixing water.

[0028] Among them, cementitious materials are also called binders. It refers to substances that can change from slurry to solid stone under physical and chemical effects, and can bind other materials to make composite solids with certain mechanical strength. Among civil engineering materials, all materials that can bond granular or block materials into a whole through a series of physical and chemical changes are collectively called cementitious materials. Commonly used cementitious materials include ordinary lime, cement, fly ash, silica fume, etc.

[0029] In certain embodiments of the present invention, the gel material comprises cement and fly ash, and the weight ratio of the cement to the fly ash is 5-10:1.

[0030] Aggregate is also called "aggregate". It is a granular material that acts as a skeleton and filler in concrete and mortar. It is generally divided into fine aggregate and coarse aggregate. The diameter of fine aggregate particles is between 0.16-5mm, and natural sand is generally used, such as river sand, sea sand and valley sand. When natural sand is lacking, artificial sand ground from hard rocks can also be used; the diameter of coarse aggregate particles is greater than 5mm, and crushed stone and pebbles are commonly used.

[0031] In certain embodiments of the present invention, the aggregate includes river sand with a fineness modulus of 2.2 and crushed stone with a particle size of 10-31.5 mm, and the weight ratio of the river sand to the crushed stone is 1:1-2.

[0032] Epoxy resin emulsion refers to epoxy resin in the form of particles, droplets or colloids dispersed in a medium with water as the continuous phase to form a stable dispersion system. Since it can be cured by polymerization reaction at room temperature and in a highly alkaline environment, it has high strength and good weather resistance after curing, and is also resistant to water, acid, alkali and most chemicals. Therefore, epoxy resin is a polymer material often used in cement mortar and concrete modification.

[0033] In certain embodiments of the present invention, the preparation method of the hydroxy acrylate emulsion is as follows:

[0034] Mix part of the mixed monomer, part of the emulsifier and water evenly, heat to 70-80°C, add part of the initiator and keep warm for 1-2 hours to obtain a seed emulsion, adjust the pH of the seed emulsion to 7-8, mix the remaining initiator with water, mix the remaining mixed monomer with the remaining emulsifier, and add the two obtained mixed solutions dropwise to the seed emulsion at the same time. Continue to keep warm for 2-4 hours, then adjust the pH of the system to 7-8, filter and discharge.

[0035] In certain embodiments of the present invention, the mixed monomer includes methyl methacrylate, butyl acrylate, methacrylic acid, and hydroxypropyl methacrylate.

[0036] In certain embodiments of the present invention, the weight ratio of methyl methacrylate, butyl acrylate, methacrylic acid, and hydroxypropyl methacrylate is 60-80:20-30:3-5:1.

[0037] Hydroxypropyl methacrylate contains hydroxyl groups, which can promote the curing of amines. This may be a bimolecular reaction mechanism, that is, the fixed hydrogen on the proton hydroxyl group first forms a hydrogen bond with the oxygen on the epoxy group, so that the epoxy group is further polarized, which is beneficial to the nucleophilic attack of the nitrogen of the amine on the epoxy carbon cation, and at the same time completes the addition of hydrogen atoms. After curing, the hydroxy acrylate emulsion and the epoxy resin emulsion can form a mutually cross-linked network. This spatial network structure connects the cement hydration products and aggregates together, improves the structural morphology of the concrete, and provides sufficient mechanical support for the concrete. The formed polymer film can improve the interface transition zone, fill the pores and microcracks inside the concrete, and play a role in waterproofing and anti-seepage. When the concrete is affected by the external environment, it is beneficial to the dispersion and transfer of stress, and prevents and weakens the growth of cracks.

[0038] In certain embodiments of the present invention, the aliphatic organic amine is one or more combinations of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, and trimethylhexamethylenediamine.

[0039] In certain embodiments of the present invention, the preparation method of epoxy basalt fiber is as follows:

[0040] The basalt fiber is hydroxylated with a piranha solution, and then dispersed in an amide organic solvent. In a protective gas atmosphere, the temperature is raised to 45-55°C, N'N-carbonyldiimidazole is added, and the reaction is stirred for 8-12 hours. Then, epichlorohydrin is added to the reaction solution, and the reaction is continued for 10-15 hours. After returning to room temperature, it is filtered, and the obtained solid is washed with ethanol and then dried.

[0041] In certain embodiments of the present invention, the preparation method of ethanolamine-modified metakaolin is as follows:

[0042] Disperse metakaolin in water to prepare a suspension, then drop an ethanolamine aqueous solution into the suspension, heat to 50-70° C., stir for 6-10 hours, filter, wash with water, and then dry.

[0043] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0044] The polycarboxylic acid water reducer and mixing water are mixed and stirred evenly to obtain a liquid premix, and then the gel material, aggregate, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix and stirred evenly to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and aliphatic organic amine are added to obtain a mixed material and mixed evenly.

[0045] The present invention also provides a cement pole, the raw materials used in the production of which include the above-mentioned high-strength impermeability concrete.

[0046] In the following examples of the present invention, cement is ordinary Portland cement with a P.O. of 42.5, Conch;

[0047] The fly ash is Class F II fly ash, with a fly ash fineness (45 μm square hole sieve residue) of 8%, a loss on ignition of <4.5%, a water requirement ratio of <97%, and a water content of <0.1%, Nanjing Hongqian Environmental Protection Engineering Co., Ltd.;

[0048] The fineness modulus of river sand is 2.2, Lingshou County Yongshun Mineral Products Processing Plant;

[0049] The crushed stone particle size is 10-31.5mm, Lingshou County Yongshun Mineral Products Processing Plant;

[0050] The epoxy resin emulsion is E44 bisphenol A type liquid epoxy resin, epoxy equivalent 210-230g / mol, Nantong Xingchen Synthetic Materials Co., Ltd.;

[0051] Hydroxyacrylate emulsion: homemade;

[0052] Triethylenetetramine: Jinan Kaichuang Chemical Co., Ltd.

[0053] Epoxy basalt fiber: homemade;

[0054] Calcium sulphoaluminate: Shandong Xinxiangda Chemical Co., Ltd.;

[0055] Ethanolamine-modified metakaolin: homemade;

[0056] Polycarboxylate water reducer: Beijing Wantuming Technology Co., Ltd.;

[0057] Mixing water: tap water.

[0058] Embodiment 1:

[0059] A high-strength impermeable concrete, comprising:

[0060] 500 parts of cement, 80 parts of fly ash, 500 parts of river sand, 980 parts of crushed stone, 120 parts of epoxy resin emulsion, 25 parts of hydroxy acrylate emulsion, 6 parts of triethylenetetramine, 70 parts of epoxy basalt fiber, 5 parts of calcium sulfoaluminate, 15 parts of ethanolamine-modified metakaolin, 3 parts of polycarboxylic acid water reducer, and 100 parts of mixing water.

[0061] Wherein, the preparation method of hydroxy acrylate emulsion is as follows:

[0062] 75 kg of methyl methacrylate, 20 kg of butyl acrylate, 5 kg of methacrylic acid, and 1 kg of hydroxypropyl methacrylate were uniformly mixed to obtain a mixed monomer;

[0063] The initiator is ammonium persulfate, weighing 464 g;

[0064] Mix 1.5 kg of sodium dodecyl sulfate SDS and 1.5 kg of OP-10 to obtain an emulsifier;

[0065] Mix 30% of mixed monomers, 30% of emulsifiers, and 43.5kg of water evenly, heat to 80°C, add 15% of initiator and keep warm for 2h to obtain seed emulsion, adjust the pH of the seed emulsion to 7-8 with saturated sodium bicarbonate solution, mix the remaining 85% of initiator with 101.5kg of water to obtain a first solution, and mix the remaining 70% of mixed monomers with 70% of emulsifier to obtain a second solution, and simultaneously add the obtained first solution and second solution dropwise to the seed emulsion, control the dropping time to be greater than 2h, continue to keep warm for 3.5h after the dropping is completed, adjust the system pH to 7-8 with ammonia water, filter with a 200-mesh gauze, and discharge.

[0066] The preparation method of epoxy basalt fiber is as follows:

[0067] 100 kg of chopped basalt fibers (length 5-50 mm, diameter 7-25 μm) were added to 250 L of piranha solution, and the fibers were subjected to ultrasonic oscillation treatment at 50 ° C for 4 h, filtered out, washed with water, and dried. The fibers were then dispersed in 250 L of DMAc. Under nitrogen protection, the temperature was raised to 50 ° C, 16.2 kg of N'N-carbonyldiimidazole was added, and the reaction was stirred for 10 h. Then, 0.93 kg of epichlorohydrin was added to the reaction solution, and the reaction was continued for 15 h. After returning to room temperature, the fibers were filtered out, and the solids were washed with ethanol and dried.

[0068] The preparation method of ethanolamine-modified metakaolin is as follows:

[0069] Disperse 25 kg of metakaolin in 100 L of water to prepare a suspension, then drop 50 mL of triethanolamine aqueous solution (2.4 kg dissolved in 8 L of water) into the suspension, heat to 60° C., stir for 8 h, filter, wash with water, and then dry.

[0070] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0071] The polycarboxylate water reducer and mixing water are mixed, stirred at a stirring speed of 400 rpm for 5 minutes to obtain a liquid premix, and cement, fly ash, river sand, crushed stone, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix, stirred at a stirring speed of 200 rpm for 25 minutes to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and triethylenetetramine are added, and stirred at a stirring speed of 200 rpm for 10 minutes.

[0072] Embodiment 2:

[0073] A high-strength impermeability concrete, comprising:

[0074] 500 parts of cement, 70 parts of fly ash, 500 parts of river sand, 1000 parts of crushed stone, 120 parts of epoxy resin emulsion, 30 parts of hydroxy acrylate emulsion, 10 parts of triethylenetetramine, 80 parts of epoxy basalt fiber, 10 parts of calcium sulfoaluminate, 20 parts of ethanolamine-modified metakaolin, 5 parts of polycarboxylic acid water reducer, and 120 parts of mixing water.

[0075] The preparation method of hydroxy acrylate emulsion, epoxy basalt fiber and ethanolamine-modified metakaolin is the same as that of Example 1;

[0076] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0077] The polycarboxylate water reducer and mixing water are mixed, stirred at a stirring speed of 400 rpm for 5 minutes to obtain a liquid premix, and cement, fly ash, river sand, crushed stone, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix, stirred at a stirring speed of 200 rpm for 25 minutes to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and triethylenetetramine are added, and stirred at a stirring speed of 200 rpm for 10 minutes.

[0078] Embodiment 3:

[0079] A high-strength impermeability concrete, comprising:

[0080] 500 parts of cement, 50 parts of fly ash, 500 parts of river sand, 900 parts of crushed stone, 100 parts of epoxy resin emulsion, 20 parts of hydroxy acrylate emulsion, 5 parts of triethylenetetramine, 50 parts of epoxy basalt fiber, 5 parts of calcium sulfoaluminate, 10 parts of ethanolamine-modified metakaolin, 1 part of polycarboxylic acid water reducer, and 100 parts of mixing water.

[0081] The preparation method of hydroxy acrylate emulsion, epoxy basalt fiber and ethanolamine-modified metakaolin is the same as that of Example 1;

[0082] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0083] The polycarboxylate water reducer and mixing water are mixed, stirred at a stirring speed of 400 rpm for 5 minutes to obtain a liquid premix, and cement, fly ash, river sand, crushed stone, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix, stirred at a stirring speed of 200 rpm for 25 minutes to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and triethylenetetramine are added, and stirred at a stirring speed of 200 rpm for 10 minutes.

[0084] Embodiment 4:

[0085] A high-strength impermeable concrete, comprising:

[0086] 550 parts of cement, 40 parts of fly ash, 500 parts of river sand, 900 parts of crushed stone, 120 parts of epoxy resin emulsion, 20 parts of hydroxy acrylate emulsion, 10 parts of triethylenetetramine, 50 parts of epoxy basalt fiber, 10 parts of calcium sulfoaluminate, 10 parts of ethanolamine-modified metakaolin, 5 parts of polycarboxylic acid water reducer, and 100 parts of mixing water.

[0087] The preparation method of hydroxy acrylate emulsion, epoxy basalt fiber and ethanolamine-modified metakaolin is the same as that of Example 1;

[0088] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0089] The polycarboxylate water reducer and mixing water are mixed, stirred at a stirring speed of 400 rpm for 5 minutes to obtain a liquid premix, and cement, fly ash, river sand, crushed stone, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix, stirred at a stirring speed of 200 rpm for 25 minutes to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and triethylenetetramine are added, and stirred at a stirring speed of 200 rpm for 10 minutes.

[0090] Embodiment 5:

[0091] A high-strength impermeable concrete, comprising:

[0092] 500 parts of cement, 100 parts of fly ash, 500 parts of river sand, crushed stone, 100 parts of epoxy resin emulsion, 30 parts of hydroxy acrylate emulsion, 5 parts of triethylenetetramine, 80 parts of epoxy basalt fiber, 5 parts of calcium sulfoaluminate, 20 parts of ethanolamine-modified metakaolin, 1 part of polycarboxylic acid water reducer, and 120 parts of mixing water.

[0093] The preparation method of hydroxy acrylate emulsion, epoxy basalt fiber and ethanolamine-modified metakaolin is the same as that of Example 1;

[0094] The preparation method of the above-mentioned high-strength impermeable concrete is as follows:

[0095] The polycarboxylate water reducer and mixing water are mixed, stirred at a stirring speed of 400 rpm for 5 minutes to obtain a liquid premix, and cement, fly ash, river sand, crushed stone, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix, stirred at a stirring speed of 200 rpm for 25 minutes to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and triethylenetetramine are added, and stirred at a stirring speed of 200 rpm for 10 minutes.

[0096] Comparative Example 1:

[0097] The method is basically the same as Example 1, except that no hydroxy acrylate emulsion is added.

[0098] Comparative Example 2:

[0099] It is basically the same as Example 1, except that a commercially available acrylic emulsion (Kehui (Henan) New Material Technology Co., Ltd.) is used instead of the hydroxy acrylic emulsion.

[0100] Comparative Example 3:

[0101] It is basically the same as Example 1, except that the basalt fiber is not subjected to epoxy modification treatment.

[0102] Comparative Example 4:

[0103] The method is substantially the same as Example 1, except that the metakaolin is not modified by ethanolamine.

[0104] Performance Test:

[0105] ① Mechanical properties test

[0106] The high-strength impermeability concrete obtained in Examples 1-5 and Comparative Examples 1-4 was subjected to a 28d compressive strength test, and the test method was based on GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test piece should be tested in time after being taken out from the curing site, and the pressure-bearing surface of the test piece should be perpendicular to the top surface during molding. The center of the test piece should be aligned with the center of the lower pressure plate of the testing machine, and the testing machine should be started. During the test, the load should be applied continuously and evenly. When the concrete strength grade is <C30, the loading speed should be 0.3-0.5Mpa per second; when the concrete strength grade is ≥C30 and <C60, the loading speed should be 0.5-0.8MPa per second; when the concrete strength grade is ≥C60, the loading speed should be 0.8-1.0MPa per second. When the test piece is close to failure and begins to deform sharply, the throttle of the testing machine should be stopped until it is destroyed. The failure load is then recorded in Table 1.

[0107] ② Water penetration resistance test

[0108] The high-strength impermeable concrete prepared in Examples 1-5 and Comparative Examples 1-4 was tested for water seepage resistance. The test method was carried out according to the water seepage height method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The water seepage height of each specimen was detected and the data were recorded in Table 1.

[0109] ③ Chloride ion penetration resistance test

[0110] The high-strength impermeable concrete prepared in Examples 1-5 and Comparative Examples 1-4 was tested for its chloride ion penetration resistance. The test method was carried out according to the RCM method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The chloride ion diffusion coefficient DRCM of each specimen was detected and the data was recorded in Table 1.

[0111] Table 1:

[0112]

[0113] It can be seen from Table 1 above that the high-strength impermeable concrete prepared by the present invention has excellent mechanical strength and excellent waterproof and impermeability performance. By comparing Example 1 with Comparative Example 1, it can be seen that the addition of hydroxy acrylate emulsion plays a positive role in improving the mechanical strength and waterproof and impermeability performance of concrete. By comparing Example 1 with Comparative Example 2, it can be seen that compared with acrylate emulsion, the hydroxy acrylate emulsion in the present invention has a better effect on improving the mechanical strength and waterproof and impermeability performance of concrete. By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that both the epoxy modification of basalt fiber and the ethanolamine modification of kaolin have played a positive role in improving the mechanical strength and waterproof and impermeability performance of concrete.

[0114] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength impermeable concrete, characterized in that: It is prepared from the following raw materials in parts by weight: 500-600 parts of gel material, 1400-1600 parts of aggregate, 100-120 parts of epoxy resin emulsion, 20-30 parts of hydroxy acrylate emulsion, 5-10 parts of aliphatic organic amine, 50-80 parts of epoxy basalt fiber, 5-10 parts of calcium sulfoaluminate, 10-20 parts of ethanolamine-modified metakaolin, 1-5 parts of polycarboxylate water reducer, and 100-120 parts of mixing water; The gel material comprises cement and fly ash, and the weight ratio of the cement to the fly ash is 5-10:1; The preparation method of the hydroxy acrylate emulsion is as follows: Mix part of the mixed monomer, part of the emulsifier and water evenly, heat to 70-80°C, add part of the initiator and keep warm for 1-2 hours to obtain a seed emulsion, adjust the pH of the seed emulsion to 7-8, mix the remaining initiator with water, mix the remaining mixed monomer with the remaining emulsifier, and drop the two obtained mixed solutions into the seed emulsion at the same time, keep warm for 2-4 hours, adjust the pH of the system to 7-8, filter and discharge; The mixed monomers include methyl methacrylate, butyl acrylate, methacrylic acid, and hydroxypropyl methacrylate; The weight ratio of methyl methacrylate, butyl acrylate, methacrylic acid and hydroxypropyl methacrylate is 60-80:20-30:3-5:1; The preparation method of the epoxy basalt fiber is as follows: Hydroxylate the basalt fiber with piranha solution, disperse it in an amide organic solvent, heat it to 45-55°C under a protective gas atmosphere, add N'N-carbonyldiimidazole, stir and react for 8-12 hours, then add epichlorohydrin to the reaction solution, continue to react for 10-15 hours, return to room temperature and filter, wash the obtained solid with ethanol and dry it; The preparation method of the ethanolamine-modified metakaolin is as follows: Disperse metakaolin in water to prepare a suspension, then drop an ethanolamine aqueous solution into the suspension, heat to 50-70°C, stir for 6-10 hours, filter, wash with water, and then dry; The aliphatic organic amine is one or more combinations of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, and trimethylhexamethylenediamine.

2. The high-strength impermeable concrete according to claim 1, characterized in that: The preparation method is as follows: The polycarboxylic acid water reducer and mixing water are mixed and stirred evenly to obtain a liquid premix, and then the gel material, aggregate, epoxy basalt fiber, ethanolamine-modified metakaolin and calcium sulfoaluminate are added to the liquid premix and stirred evenly to obtain a slurry, and finally the epoxy resin emulsion, hydroxy acrylate emulsion and aliphatic organic amine are added to obtain a mixed material and mixed evenly.

3. A cement pole, characterized in that: It comprises the high-strength impermeable concrete as described in claim 1 or 2.

Citation Information

Patent Citations

  • Modified metakaolin-based permeation-resistant and crack-resistant agent for concrete

    CN102515608A

  • C60 high-strength resin concrete as well as preparation process and application thereof

    CN114315290A

  • Anti-crack concrete with low shrinkage rate and preparation method thereof

    CN114656218A

Cited By

  • High-strength cement pole material and preparation method thereof

    CN121850543A

  • High-strength cement pole material and method for manufacturing the same

    CN121850543B